2022
DOI: 10.3390/agronomy12112701
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus velezensis Associated with Organomineral Fertilizer and Reduced Phosphate Doses Improves Soil Microbial—Chemical Properties and Biomass of Sugarcane

Abstract: Appropriately using phosphorus (P) for the fertilization of sugarcane is critical to achieving high productivity because it is one of the most limiting nutrients in agricultural cropping systems. Thus, the objective of this research was to evaluate the morphological, biochemical, and yield responses of sugarcane, and the soil microbial–chemical properties, under the use of organomineral fertilizer (OF) associated or not with Bacillus velezensis strain UFV 3918 (B) combined with mono ammonium phosphate (MAP) do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…The number of tillers per meter is a component of productivity that acts as a strong indicator of drought tolerance in sugarcane [109], showing that the increase obtained from PGPB under the 33% water regime demonstrates the tolerance-promoting potential of these species. Other studies have also reported an increase in the number of tillers under inoculation with species of the genus Bacillus [36,41,94,110].…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…The number of tillers per meter is a component of productivity that acts as a strong indicator of drought tolerance in sugarcane [109], showing that the increase obtained from PGPB under the 33% water regime demonstrates the tolerance-promoting potential of these species. Other studies have also reported an increase in the number of tillers under inoculation with species of the genus Bacillus [36,41,94,110].…”
Section: Discussionmentioning
confidence: 80%
“…In addition, the authors reported greater root growth and an increase in total dry matter in PSS treated with B. subtilis. The Bacillus genus is deeply associated with phosphorus solubilization [94] due to mechanisms such as the production of organic acids, acidification, and chelation [36,95], which increases the nutrient uptake efficiency by the roots, especially under adequate water availability.…”
Section: Discussionmentioning
confidence: 99%
“…Soil organic phosphorus accounts for 30-65%, while the remaining 35-70% is in inorganic forms. Organic phosphorus generally exists in an inert form in the soil and is fixed to form insoluble phosphorus forms, which are difficult for plants to directly absorb and use, and inorganic phosphorus easily reacts with ions in the soil, such as Fe 3+ , Al 3+ and Ca 2+ , generating insoluble phosphate; thus, the long-term application of phosphorus fertilizer overwhelmingly results in phosphate that is difficult for plants to directly absorb and cannot completely address phosphorus deficiencies in soils [6,7]. The overapplication of phosphate fertilizers can also lead to environmental problems such as negative impacts on the food chain, eutrophication, soil nutrient imbalances and destruction of the soil microbial environment.…”
Section: Introductionmentioning
confidence: 99%